Interactions between diurnal winds and floodplain mosaics control the insect boundary layer in a river corridor - Alexander N. Sukhodolov; Alessandro Manfrin; Stefano Larsen; Oleksandra O. Shumilova; Michael T. Monaghan; Klement Tockner (Aquatic Sciences, 2023)
Insect flight along river corridors is a fundamental process that facilitates sustainable succession and diversity of aquatic and terrestrial insect communities in highly dynamic fluvial environments. This study examines variations in the thickness of the insect boundary layer (i.e., the pre-surface atmosphere layer in which air velocity does not exceed the sustained speed of flying insects) caused by interactions between diurnal winds and the heterogenous habitat mosaics in the floodplain of a braided river. Based on advective–diffusive theory, we develop and test a semi-empirical model that relates vertical flux of flying insects to vertical profiles of diurnal winds. Our model suggests that, in the logarithmic layer of wind, the density of insect fluxes decreases exponentially with the altitude due to the strong physical forcing. Inside the insect boundary layer, the insect fluxes can increase with the altitude while the winds speed remains nearly constant. We suggest a hypothesis that there is a close correspondence between the height of discontinuity points in the insect profiles (e.g. points with abrupt changes of the insect flux) and the displacement heights of the wind profiles (e.g. points above which the wind profile is logarithmic). Vertical profiles were sampled during three time-intervals at three different habitat locations in the river corridor: a bare gravel bar, a gravel bar with shrubs, and an island with trees and shrubs. Insects and wind speed were sampled and measured simultaneously over each location at 1.5-m intervals up to approximately 17 m elevation. The results support our working hypothesis on close correspondence between discontinuity and displacement points. The thickness of the insect boundary layer matches the height of the discontinuity points and was about 5 m above the bare gravel bar and the gravel bar with shrubs. Above the island, the structure of the insect boundary layer was more complex and consisted of two discontinuity points, one at the mean height of the trees’ crowns (ca. 15 m), and a second, internal boundary layer at the top of the shrubs (ca. 5 m). Our findings improve the understanding of how vegetation can influence longitudinal and lateral dispersal patterns of flying insects in river corridors and floodplain systems. It also highlights the importance of preserving terrestrial habitat diversity in river floodplains as an important driver of both biotic and abiotic (i.e., morphology and airscape) heterogeneity.